Matrix protein tenascin-C expands and reversibly blocks maturation of murine eosinophil progenitors - Doan, Ton C.; Jeong, Brian M.; Coden, Mackenzie E.; Loffredo, Lucas F.; Bhattacharyya, Swati; Chiarella, Sergio E.; Varga, John; Abdala-Valencia, Hiam; Berdnikovs, Sergejs (Journal of allergy and clinical immunology, 2018)
TNC is a hexabrachion featuring epidermal growth factor–like repeats, fibronectin type III (FN3)-like repeats, and a fibrinogen-like globe that interface integrins and other matrix components in tissues.3,E5,E6 Importantly, TNC is a known hematopoietic niche component in the bone marrow stroma.4,E7 Moreover, exposing naive murine eosinophils to TNC-enriched provisional matrices significantly upregulates the gene expression of immaturity markers (Ly6a [Sca-1], CD34) and suppresses IL-5Rα (IL5ra [CD125]) expression, as determined by RNA-Seq (our unpublished data, 2018). Within the bone marrow environment, fibronectin affects progenitor fate decisions via the FN3 domain binding.7 Hyaluronic acid scaffolds are sufficient to maintain long-term cultures of CD34+ hematopoietic cells obtained from human cord blood.8 Identifying specific integrin-matrix interactions regulatory for in situ hematopoiesis of eosinophil progenitors is a subject of future studies by our group. [...]using an allergic airway inflammation model, we showed that allergen-challenged lungs of TNC-deficient (TNC−/−) mice lacked both CD45+c-kit+CD34+ common myeloid progenitors and CD45+Lin−Siglec-F+Sca-1+ eosinophil precursors compared with wild-type (WT) controls (Fig 2, C; see Fig E3 in this article's Online Repository at www.jacionline.org). Collectively, our results illustrate the significant potential of the provisional ECM to support a hematopoietic niche environment and control eosinophil progenitor in situ expansion and maturation, which has significant implications for future strategies looking to limit tissue eosinophils in allergic diseases.Methods Mouse model of allergic lung inflammation All experiments were performed with 6- to 12-week-old female C57BL/6J mice (Jackson Labs, Bar Harbor, Me) and age-matched female TNC−/− mice (C57BL/6 N-TgH, from RIKEN, Saitama, Japan).